2017
DOI: 10.1007/s11356-017-8861-4
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative study on nitrogen deposition and canopy retention in Mediterranean evergreen forests

Abstract: To assess the impact of nitrogen (N) pollutants on forest ecosystems, the role of the interactions in the canopy needs to be understood. A great number of studies have addressed this issue in heavily N-polluted regions in north and central Europe. Much less information is available for the Iberian Peninsula, and yet this region is home to mountain forests and alpine grasslands that may be at risk due to excessive N deposition. To establish the basis for ecology-based policies, there is a need to better underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 72 publications
1
11
0
Order By: Relevance
“…Wet deposition as derived from N fluxes in RF was in the same range of values reported in previous studies at La Castanya (Aguillaume, Rodrigo, & Avila, ; Avila et al, ). The N fluxes in the form of NO3- were larger in TF than RF during the study period, suggesting that dry deposition may have contributed substantially to total NO3- deposition.…”
Section: Discussionsupporting
confidence: 83%
“…Wet deposition as derived from N fluxes in RF was in the same range of values reported in previous studies at La Castanya (Aguillaume, Rodrigo, & Avila, ; Avila et al, ). The N fluxes in the form of NO3- were larger in TF than RF during the study period, suggesting that dry deposition may have contributed substantially to total NO3- deposition.…”
Section: Discussionsupporting
confidence: 83%
“…One possible explanation might be that with aging and stand decline (which was the case for the considered spruce forest), the nitrogen nutrient requirements and thus the uptake by the spruce needles decreased, explaining the increase of NO 3 − and NH 4 + in TF-S. However, in general NH 4 + was more efficiently retained in canopy than NO 3 − (Avila et al, 2017), which could explain why the increase in nitrate is higher than that in ammonia in TF-S ( Fig. 7b and d).…”
Section: Influence Of Type Of Vegetation Cover and Rainfall Amount Onmentioning
confidence: 96%
“…flux but with different percentage in agricultural, rural or urban site (58-80%; Avila et al, 2017), underlining the role played by the tree species, but also the site location (distance from urban or agricultural zone).…”
Section: Influence Of Type Of Vegetation Cover and Rainfall Amount Onmentioning
confidence: 99%
“…A multidisciplinary approach that is patent in this special issue, which opens with two articles (Lo Cascio et al 2017;Ochoa-Hueso et al 2017b) that focus primarily on the response of Mediterranean soils and soil-inhabiting communities to N deposition, is followed by three articles that focus on the usefulness of cryptogams (mosses, lichens, and liverworts) as biomarkers of increasing aridity and toxic metal pollution (Basile et al 2017;Cogolludo et al 2017;Paoli et al 2017). The issue continues with two articles by Avila et al (2017) and Cabal et al (2017) about the patterns and effects of nitrogen deposition on woody plant-dominated ecosystems from Spain and finishes with three articles focused on the effects of tropospheric ozone on larch forests (Finco et al 2017), crops (Marzuoli et al, 2016), and pasture species (González-Fernández et al 2017). Soil is a crucial part of all the terrestrial ecosystems and a particularly complex one.…”
mentioning
confidence: 99%
“…The role of the interactions between the canopy and N pollutants is one of them. In this issue, Avila et al (2017) measured N deposition (as bulk, wet, and throughfall fluxes of dissolved inorganic N) and air N gas concentrations from 2011 to 2013 at four Spanish holm-oak (Quercus ilex) sites characterized by different land use. The results showed that canopies retained both NH 4 -N and NO 3 -N, with a higher retention at the agricultural and rural sites than at sites located close to big cities, highlighting the role of the forest canopy in processing N pollutant emissions.…”
mentioning
confidence: 99%